Leukemia inhibitory factor promotes nasopharyngeal carcinoma progression and radioresistance - Liu, Shu-Chen; Tsang, Ngan-Ming; Chiang, Wen-Che; Chang, Kai-Ping; Hsueh, Chuen; Liang, Ying; Juang, Jyh-Lyh; Chow, Kai-Ping N.; Chang, Yu-Sun (The Journal of clinical investigation, 2013)
Radioresistance of EBV-associated nasopharyngeal carcinoma (NPC) is associated with poor prognosis for patients with this form of cancer. Here, we found that NPC patients had increased serum levels of leukemia inhibitory factor (LIF) and that higher LIF levels correlated with local tumor recurrence. Furthermore, in vitro studies with NPC cells and in vivo xenograft mouse studies demonstrated that LIF critically contributes to NPC tumor growth and radioresistance. Using these model systems, we found that LIF treatment activated the mTORC1/p70S6K signaling pathway, enhanced tumor growth, inhibited DNA damage responses, and enhanced radioresistance. Treatment with either soluble LIF receptor (sLIFR), a LIF antagonist, or the mTOR inhibitor rapamycin reversed LIF-mediated effects, resulting in growth arrest and increased sensitivity to γ irradiation. Immunohistochemical (IHC) analyses of human NPC biopsies revealed that LIF and LIFR were overexpressed in tumor cells and that LIF expression correlated with the presence of the activated p-p70S6K. Finally, we found that the EBV-encoded protein latent membrane protein 1 (LMP1) enhances LIF production. Together, our findings indicate that LIF promotes NPC tumorigenesis and suggest that serum LIF levels may predict local recurrence and radiosensitivity in NPC patients.